Dreams and deeds : achievement motivation in Nigeria - LeVine, Robert Alan (Chicago : University of Chicago Press, 1966)
This study examines the psychological factors in economic development and African attitude towards work environment.
Includes index
Includes bibliographical footnotes.
sju 23/01/2019
Loans
Keywords: National characteristics, Nigerian; Achievement motivation